Métodos de coleta de dados: análise comparativa dos perfis dos respondentes e dos resultados obtidos via internet e via presencial face a face - Calliyeris, Vasiliki Evangelou (2012)
This work has as objective analyze comparatively the respondents profile and the results obtained by two different data collection approaches: by internet (online) and face to face at home (offline). The criteria selected for this comparison were the response return rate for both methods, the answers quality obtained on the attributes evaluation questions and the results on habits and attitudes of the selected samples. The first two chosen criteria refer to a topic very discussed in the academy that is the relationship between the respondent and the electronic data collection method, on which is believed to be uncontrolled, causing low access rate and also compromising the quality of data collected. The last criteria selected refers to another theme approached by academics which is the respondents profile that both data collection methods reach, which is believed to be distinctive and in consequence, provides differences in consumption behavior of the approached targets. To reach the proposed objectives, initially some in depth exploratory interviews were conducted with executives of research institutes acting in Brazil, aiming to understand their point of view regarding the capability of the online research method. Subsequently a quantitative study was conducted through two data collection methods, electronic by internet and face to face at home, with two different samples, which results were compared. The hypotheses were confirmed once there were differences in answers return rates, bias on attributes evaluation caused by one of the targets and also differences in both social-demographic profiles that reflected in discriminant consumption habits and attitudes. This work is justified in a way that it presents a current and controversial subject in the academy and in the business world, which focus is debate the replace of the traditional date collection methods by the contemporary one by internet, or even its complementarity, in a moment that the virtual network is increasing its penetration in the relationship company-consumer